The Cacti Microbiome: Interplay between Habitat-Filtering and Host-Specificity - Fonseca-García, Citlali; Coleman-Derr, Devin; Garrido, Etzel; Visel, Axel; Tringe, Susannah G.; Partida-Martínez, Laila P. (Frontiers in Microbiology, 2016)
Cactaceae represents one of the most species-rich families of succulent plants native to arid and semi-arid ecosystems, yet the associations Cacti establish with microorganisms and the rules governing microbial community assembly remain poorly understood. We analyzed the composition, diversity and factors influencing above- and below-ground bacterial, archaeal and fungal communities associated with two native and sympatric Cacti species: Myrtillocactus geometrizans and Opuntia robusta. Phylogenetic profiling showed that the composition and assembly of microbial communities associated with Cacti were primarily influenced by the plant compartment; plant species, site and season played only a minor role. Remarkably, bacterial and archaeal diversity was higher in the phyllosphere than in the rhizosphere of Cacti, while the opposite was true for fungi. Semi-arid soils exhibited the highest levels of microbial diversity whereas the stem endosphere the lowest. Despite their taxonomic distance, M. geometrizans and O. robusta shared most microbial taxa in all analyzed compartments. Influence of the plant host did only play a larger role in the fungal communities of the stem endosphere. These results suggest that fungi establish specific interactions with their host plant inside the stem, whereas microbial communities in the other plant compartments may play similar functional roles in these two species. Biochemical and molecular characterization of seed-borne bacteria of Cacti supports the idea that these microbial symbionts may be vertically inherited and could promote plant growth and drought tolerance for the fitness of the Cacti holobiont. We envision this knowledge will help improve and sustain agriculture in arid and semi-arid regions of the world.